2009
DOI: 10.1186/1758-3284-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Grading systems in head and neck dysplasia: their prognostic value, weaknesses and utility

Abstract: BackgroundGrading of dysplasia, including head and neck lesions, continues to be a hotly debated subject. It is subjective and lacks intra- and inter-observer reproducibility due to the insufficiency of validated morphological criteria and the biological nature of dysplasia. Moreover, due to the absence of a consensus, several systems are currently employed.ObjectivesThe aims of this review are to:1) Highlight the significance of dysplasia and the importance of a valid method for assessing precursor lesions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 60 publications
(84 reference statements)
1
78
0
5
Order By: Relevance
“…4,6,16,23 Gale et al 16 concluded that the results of a long-term follow-up study of 1268 patients once again justify the proposal of the Ljubljana classification. It entails dividing the morphological criteria into two basic groups: benign (squamous hyperplasia and basal/ parabasal hyperplasia) and potentially malignant (atypical hyperplasia).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,6,16,23 Gale et al 16 concluded that the results of a long-term follow-up study of 1268 patients once again justify the proposal of the Ljubljana classification. It entails dividing the morphological criteria into two basic groups: benign (squamous hyperplasia and basal/ parabasal hyperplasia) and potentially malignant (atypical hyperplasia).…”
Section: Discussionmentioning
confidence: 99%
“…4,18,19 In the 'high-risk' group, the three-grade system additionally distinguishes mild and moderate dysplasia from severe dysplasia, carcinoma in situ, and squamous cell carcinoma (World Health Organization); it also distinguishes SIN 1 and 2 from SIN 3 and squamous cell carcinoma (Squamous Intraepithelial Neoplasia), and it differentiates (atypical hyperplasia) dysplasia from carcinoma in situ and squamous cell carcinoma (Ljubljana). This further differentiation was made because in daily practice normal histology, inflammation, and hyperplasia (green segment in Table 2) are generally considered to require no periodic observation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SCC develops in 6% to 20% of dysplastic lesions but dysplasia grading is not an accurate predictor. Most OPMD remain unchanged or regress (2) and dysplasia grading has been criticized as subjective, poorly reproducible, and inadequate for clinical management (3)(4)(5). There is a need for better predictive markers of transformation to guide treatment (6).…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6,7 Hyperkeratotic lesions without dysplasia can also show malignant transformation. 8 The ability of current clinical and histological methods to predict premalignant lesions that will undergo malignant transformation is limited, and it is important to develop other methods for predicting the malignant potential of lesions so that they can be treated appropriately.…”
Section: Introductionmentioning
confidence: 99%